Global warming drives a threefold increase in persistence and 1 ° C rise in intensity of marine heatwaves - Marta Marcos; Angel Amores; Miguel Agulles; Jon Robson; Xiangbo Feng (Proceedings of the National Academy of Sciences, 2025)
Marine heatwaves are extreme climatic events consisting of persistent periods of warm ocean waters that have profound impacts on marine life. These episodes are becoming more intense, longer, and more frequent in response to anthropogenic global warming. Here, we provide a comprehensive and quantitative assessment on the role of global warming on marine heatwaves. To do so, we construct a counterfactual version of observed global sea surface temperatures since 1940, corresponding to a stationary climate without the effect of long-term increasing global temperatures, and use it to calculate the contribution of global air temperature rise on the intensity and persistence of marine heatwaves. We determine that global warming is responsible for nearly half of these extreme events and that, on a global average, it has led to a three-fold increase in the number of days per year that the oceans experience extreme surface heat conditions. We also show that global warming is responsible for an increase of 1 ° C in the maximum intensity of the events. Our findings highlight the detrimental role that human-induced global warming plays on marine heatwaves. This study supports the need for mitigation and adaptation strategies to address these threats to marine ecosystems.